Improving Critical Thinking Skills of Junior High School Students in Science Learning Using the Development of Interactive E-Module Based Macromedia Flash - Vinandani Meryastiti; Zainur Rasyid Ridlo; Supeno Supeno; Rahayuningsih Rahayuningsih (Universitas Negeri Semarang, 2023)
The aim of this research is improving student critical thinking skills using interactive E-module based on macromedia flash. Critical thinking skills are one of the 4C skills students need to have in dealing with 21st century learning. Critical thinking skills is the ability to think reflectively and deeply in obtaining relevant information or knowledge and being able to make conclusions or decisions correctly and appropriately. Science teacher at SMPN 3 Jember has never trained a student's critical thinking skills through the learning process and has never done research on class 7 student skills. Vastly improved technology can be used in education to develop the taught materials of modules called e-modules. The study aims to determine the validity, practicality, and effectiveness of an interactive e-module based on macromedia flash to improve the critical thinking skills of junior high school students in science learning. The type of research used is research and development with the ADDIE development model consisting of the analysis, design, development, implementation, and evaluation. The results showed that 1) the interactive e-module based on macromedia flash was declared very valid with a percentage of 93%, 2) the practicality of interactive e-module based on macromedia flash was declared very good with a percentage of 95.2%, and 3) the interactive e-module based on macromedia flash was declared effective for improving students' critical thinking skills with an n-gain value of 0.4 belonging to the medium category and getting a positive response from students with percentage of 81.25% which was classified as positive category. Based on the results of the study, the interactive e-modules based on macromedia flash is effective in improving students' critical thinking skills.